An artificial metalloenzyme for carbene transfer based on a biotinylated dirhodium anchored within streptavidin. Issue 9 (20th April 2018) - Zhao, Jingming; Bachmann, Daniel G.; Lenz, Markus; Gillingham, Dennis G.; Ward, Thomas R.
Abstract : We report an artificial carbenoid transferase which combines a biotinylated dirhodium moiety within streptavidin scaffold. Abstract : We report on artificial metalloenzymes that incorporate a biotinylated dirhodium core embedded within engineered streptavidin (Sav hereafter) variants. The resulting biohybrid catalyzes the carbene insertion in C–H bonds and olefins. Chemical- and genetic optimization allows to modulate the catalytic activity of the artificial metalloenzymes that are shown to be active in the periplasm of E. coli (up to 20 turnovers).